Diseño del sistema integrado de gestión QHSE para car Hyundai S.A. – Bogotá D.C. - Beltrán Gómez, Andrea Carolina; Flórez Lineros, Gloria Cristina; Omaña Gutiérrez, Marie Elaine; Rodríguez Ortíz, Andry Julieth (Escuela Colombiana de Ingeniería Julio Garavito, 2015)
The purpose of this project was to design the integrated QHSE management system for Car Hyundai S.A. It was developed in the Car Hyundai facilities located in the Autopista Norte, Calle 233, Costado Occidental in the city of Bogotá in the after-sales service, to respond to the need to establish clear guidelines regarding the quality of the services provided, know and manage environmental aspects and impacts derived from the processes carried out, and the identification of hazards present in the activities and the management of risks. The investigation was framed in an exploratory-descriptive methodology approach. For the collection of the information, the interview technique was used, whose instrument was the checklist applied to key persons to identify the main processes, aspects and environmental impacts and the dangers present in the after-sales process. Likewise, a checklist was used, leveraging the techniques of observation and interview, in order to determine the degree of non-compliance with the requirements of the standards NTC-ISO 9001: 2008, NTC-ISO 14001: 2004, NTC-OHSAS 18001: 2007 and Decree 1443 of 2014 repealed by Decree 1072 of 2015. Then the system integration was presented, for which a table containing the correspondences of the requirements of the standards was created, indicating which the company owns, which must be developed and which ones are presented as an option of the integrated management system. Once the information collected was analyzed, the feasibility of integrating quality, environmental, and occupational health and safety management systems was determined, provided that the company has the necessary resources. The work to be done for the integration will be arduous especially in the environmental aspect, whose percentage of compliance with the requirements is low. With regard to occupational health and safety, in one way or another, the requirements must be met, since these are regulated by Decree 1072 of 2015. In any case, the success of the system will depend on commitment and participation. active of each and every one of the members of the company and in this way establish and maintain the integrated QHSE management system.

El presente proyecto tuvo como propósito realizar un diseño del sistema integrado de gestión QHSE para Car Hyundai S.A. Se desarrolló en las instalaciones de Car Hyundai ubicadas en la Autopista Norte, Calle 233, Costado Occidental en la ciudad de Bogotá en el servicio de postventa, para dar respuesta a la necesidad de establecer lineamientos claros en cuanto a la calidad de los servicios prestados, conocer y gestionar los aspectos e impactos ambientales derivados de los procesos realizados, y la identificación de peligros presentes en las actividades y la gestión de los riesgos. La investigación se enmarcó en un enfoque de metodología exploratoria-descriptiva. Para la recolección de la información se usó la técnica de la entrevista cuyo instrumento fue la lista de cotejo aplicada a personas claves para identificar los principales procesos, aspectos e impactos ambientales y los peligros presentes en el proceso de postventa. Igualmente se empleó una lista de verificación apalancándose en las técnicas de la observación y la entrevista, con el fin de determinar el grado de incumplimiento de los requisitos de las normas NTC-ISO 9001:2008, NTC-ISO 14001:2004, NTC-OHSAS 18001:2007 y Decreto 1443 de 2014 derogado por el Decreto 1072 de 2015. Luego se procedió a presentar la integración del sistema, para lo cual se creó un cuadro contentivo de las correspondencias de los requisitos de las normas, señalando cuales la empresa posee, cuales debe desarrollar y cuales se les presenta como opción del sistema integrado de gestión. Una vez analizada la información recabada, se determinó la viabilidad de integrar los sistemas de gestión de la calidad, ambiental y de seguridad y salud ocupacional siempre y cuando la empresa cuente con los recursos necesarios. El trabajo a realizar para la integración será arduo sobretodo en el aspecto ambiental, cuyo porcentaje de cumplimiento de los requisitos es bajo. En lo que respecta a seguridad y salud ocupacional, de alguna u otra forma se debe cumplir los requisitos, puesto que estos están reglamentados por el hoy Decreto 1072 de 2015. En cualquier caso, el éxito del sistema va a depender del compromiso y la participación activa de todos y cada uno de los integrantes de la empresa y de este modo establecer y mantener el sistema integrado de gestión QHSE.
Keywords: Calidad; Sistemas de Gestión de la Calidad; Quality; Quality Management Systems